2015
DOI: 10.1016/j.micres.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae O antigen loss alters the outer membrane protein composition and the selective packaging of proteins into secreted outer membrane vesicles

Abstract: Klebsiella pneumoniae is a nosocomial pathogen which naturally secretes lipopolysaccharide (LPS) and cell envelope associated proteins into the environment through the production of outer membrane vesicles (OMVs). The loss of the LPS O antigen has been demonstrated in other bacterial species to significantly alter the composition of OMVs. Therefore, this study aimed to comprehensively analyze the impact of O antigen loss on the sub-proteomes of both the outer membrane and secreted OMVs from K. pneumoniae. As d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 66 publications
3
40
0
2
Order By: Relevance
“…The protein composition of OMVs is known to differ from that of the source outer membrane. The contents of OMVs are known to be selectively packaged, enriching in molecules that may impact inflammation (20,34). Therefore, we tested the proinflammatory cytokine responses of macrophages exposed to enriched total outer membrane from strains expressing neither porin, either porin, or both porins to determine if the responses were similar.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The protein composition of OMVs is known to differ from that of the source outer membrane. The contents of OMVs are known to be selectively packaged, enriching in molecules that may impact inflammation (20,34). Therefore, we tested the proinflammatory cytokine responses of macrophages exposed to enriched total outer membrane from strains expressing neither porin, either porin, or both porins to determine if the responses were similar.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in a number of Gram-negative species have demonstrated that proteins are selectively packaged and concentrated into outer membrane vesicles (16,20,37). This enrichment effect is central to OMVs' role in bacterial pathogenesis.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…In several bacterial genera, such as Klebsiella and Porphyromonas, mutations that modify the O antigen have been reported to affect OMVs by altering the protein content and reducing OMV production, respectively (41,42). Similarly, while Pseudomonas O-antigen mutants have no effect on the rate of OMV release, they do affect both their contents and size (43).…”
Section: Discussionmentioning
confidence: 99%